A Survey of the Gene Repertoire of Gigaspora rosea Unravels Conserved Features among Glomeromycota for Obligate Biotrophy - Tang, Nianwu; San Clemente, Hélène; Roy, Sébastien; Bécard, Guillaume; Zhao, Bin; Roux, Christophe (Frontiers in Microbiology, 2016)
Arbuscular mycorrhizal (AM) fungi are a diverse group of soil fungi (Glomeromycota) that form the most ancient mutualistic association termed arbuscular mycorrhizal symbiosis with a majority of land plants, improving their nutrition uptake and resistance to stresses. In contrast to their great ecological implications, the knowledge of the molecular biological mechanisms involved is still scant, partly due to the limited genomic resources available. Here, we describe the gene repertoire of a new AM fungus Gigaspora rosea (Diversisporales). Among the 86332 nonredundant virtual transcripts assembled, 15346 presented similarities with proteins in the Refseq database and 10175 were assigned with GO terms. KOG and Interpro domain annotations clearly showed an enrichment of genes involved in signal transduction in G. rosea. KEGG pathway analysis indicates that most primary metabolic processes are active in G. rosea. However, as for R. irregularis, several metabolic genes were not found, including the fatty acid synthase gene. This finding supports the hypothesis that AM fungi depend on the lipids produced by their hosts. Furthermore, the presence of a large number of transporters and hundreds of secreted proteins, together with the reduced number of plant cell wall degrading enzymes could be interpreted as an evolutionary adaptation to its mutualistic obligate biotrophy. The detection of meiosis-related genes suggests that G. rosea might use a cryptic sexual process. Lastly, a phylogeny of basal fungi clearly shows Glomeromycota as a sister clade to Mucoromycotina, not only to the Mucorales or Mortierellales. The characterization of the gene repertoire from an AM fungal species belonging to the order of Diversisporales and its comparison with the gene sets of R. irregularis (Glomerales) and Gigaspora margarita (Diversisporales), reveal that AM fungi share several features linked to mutualistic obligate biotrophy. This work contributes to lay the foundation for forthcoming studies into the genomics of Diversisporales, and also illuminates the utility of comparing gene repertoires of species from Diversisporales and other clades of Glomeromycota to gain more insights into the genetics and evolution of this fungal group.